PENGARUH MODEL KOOPERATIF TIPE THINK PAIR SHARE BERBANTUAN VIDEO PEMBELAJARAN TERHADAP HASILBELAJAR DAN SIKAP SISWA PADA MATERI SISTEM REPRODUKSI PADA MANUSIA - Roma Sagala; Ely Djulia (Jurnal Pelita Pendidikan, 2016)
This study aims to determine whether there are significant influence in learning outcomes and attitude use type of the Think-Pair-Share cooperative learning model with video learning on the subject Human Reproduction System at the High School Class XI IPA 1 Katolik 1 Kabanjahe Lessons Year 2015/2016. The population in this study were all students in grade XI IPA SMA Katolik 1 Kabanjahe Lessons Year 2015/2016 lesson that consists of 4 class. Samples taken with a random samples study by the number of student 66 people. Class XI IPA 4 with the type of the TPS (Think-Pair-Share) cooperative learning model and  students as many as 33 people while XI IPA 2 with the type conventional of students as many as 33 people. This type research is experimental research. While based on the averages student seen any infuence in learning outcomes and attitude the average student in Think-Pair-Share (TPS) or experiment classroom at 81,39 with a SD 7,97. While the mean value – the average students in control classroom at 76,76 with a SD 9,01. The existence of influence in learning outcomes is also proven through testing to make use of hypothesis testing-t and the confidence level α = 0,05, where thit > ttab (2,263 > 2,002),which means in this study while accepting Ha and rejected H0. Averages student on attitude in experiment classroom 60,75% and in control class 55,45%. So it can be concluded that there was a influence in learning outcomes between types Think-Pair-Share (TPS) cooperative learning models with video learning on the subject Human Reproduction System at the state high school class XI IPA SMA Katolik 1 Kabanjahe Lessons Year 2015/2016. Keywords: Learning Outcomes, Think-Pair-Share, Human Reproduction System